2002
DOI: 10.1016/s0006-3495(02)75478-7
|View full text |Cite
|
Sign up to set email alerts
|

Temperature Dependence of Protein Dynamics: Computer Simulation Analysis of Neutron Scattering Properties

Abstract: The temperature dependence of the internal dynamics of an isolated protein, bovine pancreatic trypsin inhibitor, is examined using normal mode analysis and molecular dynamics (MD) simulation. It is found that the protein exhibits marked anharmonic dynamics at temperatures of approximately 100-120 K, as evidenced by departure of the MD-derived average mean square displacement from that of the harmonic model. This activation of anharmonic dynamics is at lower temperatures than previously detected in proteins and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
100
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 89 publications
(113 citation statements)
references
References 40 publications
13
100
0
Order By: Relevance
“…A second inflection in atomic MSDs, which is hydration-independent, was observed at a temperature between 100 and 150 K (10,18). The low temperature inflection that occurs even in dry samples was also seen in molecular dynamics (MD) simulations (19) and has been attributed to the onset of methyl group rotations (20,21).…”
mentioning
confidence: 81%
“…A second inflection in atomic MSDs, which is hydration-independent, was observed at a temperature between 100 and 150 K (10,18). The low temperature inflection that occurs even in dry samples was also seen in molecular dynamics (MD) simulations (19) and has been attributed to the onset of methyl group rotations (20,21).…”
mentioning
confidence: 81%
“…many hundreds of molecules) and long simulation times can now be addressed (e.g. Smith, 1991;Tarek et al, 2001;Tarek and Tobias, 2002;Hayward and Smith, 2002;Wood et al, 2007;Meinhold et al, 2007;Marrink et al, 2007). The dashed rectangle in Fig.…”
Section: Membrane Dynamicsmentioning
confidence: 99%
“…Subsequently, a number of neutron scattering and other experimental and computer simulation studies on various biological systems have revealed that many proteins exhibit this temperature-dependent dynamical transition around 180-220K (12,13,(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31).…”
Section: Dynamics Protein Glass Transitionmentioning
confidence: 99%
“…However, neutron scattering experiments and molecular dynamics simulations have shown signatures of anharmonic dynamics well below the ~220K dynamical transition (24,(29)(30)(31). The dynamic processes associated with this low-temperature anharmonicity, and how these motions may be related to global dynamical changes at the dynamical transition, have yet to be fully understood.…”
Section: Dynamics Protein Glass Transitionmentioning
confidence: 99%